Late-stage lipidation of fully elaborated tryptophan-containing peptides for improved pharmacokinetics. Issue 12 (22nd March 2017) - Huang, Chunhui; Wille, Cannon B.; He, Huaibing; Reddy, Vijay Bhasker Gangula; Nargund, Ravi P.; Lin, Songnian; Palani, Anandan
Graphical abstract: Highlights: Selective tryptophan functionalization was applied in non-protected peptides with native sequence. The model peptide modified through tryptophan late-stage lipidation conserved bioactivity. Peptide glucagon with lipidation on tryptophan shown a greatly improved pharmacokinetic profile. Abstract: The late-stage modification of native peptides to alter and/or enhance their properties and functions is attractive but formidably challenging. Peptide lipidation is one of the effective strategies to overcome short half-life and rapid clearance. Herein, we report a late-stage installation of a fatty acid lipid onto fully elaborated peptides, using glucagon as an example, through regio- and chemoselective functionalization of tryptophan with high potency and remarkable in vivo half-life extension.